(untitled) (Faridpur Medical College Journal, 2012)
Cleft lip and cleft palate has been a recognized congenital malformation from a very early stage in recorded history. The infant born with an orofacial deformity, which leads to develop an unwilling psychosocial problem among the parents and also among the relatives. Successful treatment of cleft is based on overcoming in tissue shortage and repositioning of the tissues in normal anatomical pattern so that it restores both appearance and function. Various modalities of theme, works, observations and involvement of multidisciplinary approaches were tried to achieve better cosmetic, aesthetic and functional aspect in management of cleft face. Poorly performed primary surgery carries a high risk of iatrogenic disturbances of subsequent orofacial growth. Delayed nasal repair in patient with cleft lip did not produce satisfactory aesthetic and functioning result. Aim & objective of the study is to achieve a cosmetically well-accepted face in respect to lip, philtrum and nose of both sides after cleft lip surgery and to reduce the incidence of secondary correction of deformed nose in a patient with cleft lip. In our study total 86 cases are studied according to preformed inclusion and exclusion criteria. Simultaneous correction of alar cartilage deformity at the time of primary repair of cleft lip may lessen the staged operative procedure and markedly reduce the economic burden to the family. DOI: http://dx.doi.org/10.3329/fmcj.v7i1.10291 Faridpur Med. Coll. J. 2012;7(1): 13-17